Cytochrome P450 loss-of-function polymorphism genotyping on the Agilent Bioanalyzer and clinical application. (December 2009) - Piatkov, Irina; Jones, Trudi; Rochester, Colin
Responses to toxins and drugs, even to standard medical drug treatment regimens, can vary significantly between individuals. Similar dosages can have divergent results due to polymorphisms in the genes that code for the enzymes responsible for the metabolism of drugs. The focus of this report is to describe our exploration of the personalized medicine approach for patient care at Sydney West Area Health Service. We would like to demonstrate the importance of this approach as it is the subject of debate in the medical and scientific community. The critical points in this debate are the cost of testing, laboratory space required and clinical application. We have shown that a simple approach and instruments like the Agilent Bioanalyzer could be cost effective for laboratory operation. The Agilent Bioanalyzer (Agilent Technologies, CA, USA) can be used for proteins, DNA and cell studies. Hence, reduced cost of instruments, laboratory space requirements, maintenance and operational costs are great advantages of this technology, especially for development and research laboratories.